Beyond the standard model of elementary particle physics - Nagashima, Yorikiyo (Weinheim, Germany : Wiley-VCH Verlag, 2014)
"A unique and comprehensive presentation on modern particle physics which stores the background knowledge on the big open questions beyond the standard model, as the existence of the Higgs-boson, or the nature of Dark Matter and Dark Energy"--Provided by publisher.
Higgs -- Neutrino -- Grand unified theories -- Supersymmetry I: basics -- Supersymmetry II: phenomenology -- Extra dimensions -- Cosmology I: big bang universe -- Cosmology II: structure formation -- Dark matter -- Dark energy -- Appendix A: Virial theorem -- Appendix B: Chandrasekhar mass -- Appendix C: Production of KK gravitons -- Appendix D: Homotopy -- Appendix E: General relativity -- Appendix F: Tensor spherical harmonic function -- Appendix G: Destiny of the cosmos -- Appendix H: Answers to some problems.
Edition statement from running title area.
Includes bibliographical references and index.
Online resource; title from PDF title page (ebrary, viewed April 02, 2014).
Keywords: Nuclear astrophysics; Particles (Nuclear physics); Nuclear astrophysics; Physics; Quantum electrodynamics; SCIENCE -- Physics -- Quantum Theory; Nuclear astrophysics; Particles (Nuclear physics); Electronic books